RESTATEMENT TENTANG YURIDIKSI PERADILAN MENGADILI PERBUATAN MELAWAN HUKUM PEMERINTAH - Enrico Simanjuntak (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2019)
Administration Act concerns the extent to which the scope of court jurisdiction relating administrative torts (onrechtmatige overheidsdaad), as intended in Article 1365 of the Civil Code. There are at least two different views on the issue. First, administrative court mutatis mutandis has the power to resolve the case relating onrechtmatige overheidsdaad, this view is represented by Supreme Court Circular No. 4/2016. A different view holds that the onrechtmatige overheidsdaad act is a genus whereas the factual act as referred to UUAP is a species. This second view is not mutatis mutandis transferring the authority of civil judges to administrative court try the onrechtmatige overheidsdaad case. This difference of opinion is important to be studied more thoroughly to know the real issue of the different views.